Hubungan Kadar Hemoglobin dengan Kejadian Dismenore pada Mahasiswa Tingkat Satu Program Studi Kebidanan Magelang Poltekkes Kemenkes Semarang - Maulita Ardhana; Tulus Puji Hastuti (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2018)
The problems usually faced by women during menstruation : amenorhea (menstruation doesn’t occur), premenstrual syndrome (tension before menstruation), abnormal uterinebleeding, disfungtion uterine bleeding, and dysmenorrhea (the pain during menstruation) (Price and Wilson, 2006). Forty to seventy percent women in their reproductive age have dysmenorrhea, and only ten percent that spoil their daily activities. Studied Result that was done by researcher on 20th of January 2014 towards to freshmen of Magelang Midwifery Studies Program Polytechnic Semarang Ministry of Health, shows that there are eight students have dysmenorrhea, six of them have dysmenorrhea with anemia. The purpose of this research is to know the relation between the level of hemoglobin and the dysmenorrhea case. The research type is analytic that is to know the relation between hemoglobin level with the dysmenorrhea case. The population of the research is all freshmen of Magelang Midwifery Studies Program that there are 119 students, 30 student samples were taken, hopefully it has coverred all exist population. Because of the limited time, limited researcher and cost so that the researcher uses sample population methode by Simple Random Sampling Technic and with checklist measuring tools as dysmenorrhea measuring tool and Haemometer digital as hemoglobin level measuring tools. The relation test result by using Kolmogorov-Smimov test, we get the result the p = 0.024 and p < 0.05 then it shows that there is relation between hemogobin level with dysmenorrhea case. This study resultsare expected tobean effort to raiseawareness and preventionof anemiaprevention will be one factor inthe occurrence of dysmenorrhea.